A novel, stain-free, natural auto-fluorescent signal, Sig M, identified from cytometric and transcriptomic analysis of infectivity of Cryptosporidium hominis and Cryptosporidium parvum - Ogbuigwe, Paul; Roberts, Joanna M.; Knox, Matthew A.; Heiser, Axel; Pita, Anthony; Haack, Neville A.; Garcia-Ramirez, Juan Carlos; Velathanthiri, Niluka; Biggs, Patrick J.; French, Nigel P.; Hayman, David T. S. (Frontiers in Cellular and Infection Microbiology, 2023)
Cryptosporidiosis is a worldwide diarrhoeal disease caused by the protozoan Cryptosporidium. The primary symptom is diarrhoea, but patients may exhibit different symptoms based on the species of the Cryptosporidium parasite they are infected with. Further, some genotypes within species are more transmissible and apparently virulent than others. The mechanisms underpinning these differences are not understood and an effective in vitro system for Cryptosporidium culture would help advance our understanding of these differences. Using COLO-680N cells, we employed flow cytometry and microscopy along with the C. parvum-specific antibody Sporo-GloTM to characterise infected cells 48hrs following infection with C. parvum or C. hominis. Cryptosporidium parvum-infected cells showed higher levels of signal using Sporo-GloTM than C. hominis infected cells, likely because Sporo-GloTM was generated against C. parvum. We found a subset of cells from infected cultures that expressed a novel, dose-dependent auto-fluorescent signal that was detectable across a range of wavelengths. The population of cells that expressed this signal increase proportionately to multiplicity of infection (MOI). Spectral cytometry confirmed the signature of this subset of host cells closely matched that of oocysts present in the infectious ecosystem, pointing to a parasitic origin. Present in both C. parvum and C. hominis cultures, we named this Sig M and due to its distinct profile in cells from both infections, it could be a better marker for assessing Cryptosporidium infection in COLO-680N cells than Sporo-GloTM. We also noted SigM’s impact on Sporo-GloTM detection as Sporo-GloTM uses fluoroscein–isothiocynate (FITC), which is detected where SigM also fluoresces. Lastly, we used NanoString nCounter® analysis to investigate the transcriptomic landscape for the two Cryptosporidium species, assessing gene expression of 144 host and parasite genes. Despite host gene expression at high levels, the levels of putative intracellular Cryptosporidium gene expression were low, with no significant difference from controls, which could be in part be explained by the abundance of uninfected cells present as determined by both Sporo-GloTM and Sig M analysis.